The Kind Stranger - Dania, Deji (Literamed Publications Nigeria Limited, 2009)
Along the highway from Jerusalem to Jericho,wicked robbers beat up a traveler and leave him wounded and almost dead.Two holy men who pass by afterwards didn't stop to help him.It seems he would surely die,but soon, a kind stranger comes along.
Keywords: Christianity; Bible Stories; Religion